Follow

# How do you come up with so many stories and where do you find inspiration for all of your characters?

View Full Interview Answered

# Graph Y equals x plus 4?

An easy way of solving this equation involves the use of a table. List several arbitrary x values on the left side and then their respective y values in the right side of the …table: X Y 0 4 1 5 2 6 3 7 4 8 5 9 With the x and y values shown on the above chart, plot these values on a graph and it will depict a diagonal line intersecting the y-axis at 4 and intersecting the x-axis at -4. (MORE)

Answered

# What is a 4 x 4 vehicle?

A vehicle where all four wheels are driven. Most cars only have two wheels that rotate via the engine and propel it along, the other two just hold up the corners. Having all f…our wheels driven, gives greater grip and more traction in slippery conditions in commercial vehicles, or better stabilty round corners in sports cars. It's pronounced 'Four by Four' and like the animals that went in 'two by two' into the Arc, all four wheels drive 'four by four'. (MORE)

Answered

# How do you graph cos x plus pie divided by 4?

amplitude=1 period=2 pi phase shift=0 vertical translation=pi/4 it will start at (0,1) on the y-axis and cross through pi on the x-axis, then the min will be in the mi…ddle of pi and 2 pi at -1. there will be one complete wave to 2 pi on your graph (one curve on top and one on bottom of the x-axis), but then you need to shift it to the left, so that the graph will start at (0,-1). (MORE)

Answered

# X plus 4 x plus 5?

x+4x=5 if x=1 then substitute the value of x to the given equation.... 1+4(1)=5 5=5

Answered

In Education

# Is the equation x plus y equals 4 linear or not?

It is linear. The highest power is 1 (x = x1, y = y1) so it is linear.

Updated Answer

In Education

# What are the factors of 3x squared minus x plus 4?

That doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (1 plus or minus the square root of -47) divided by 6. x = 0.16666 + 1.14260910…0066840i = 1st root = r1 x = 0.16666 - 1.142609100066840i = 2nd root = r2 where i is the square root of negative one. Then factor as (x - r1)(x - r2) Or you can complete the square to transform the trinomial into the difference of the squares 3x2 - x + 4 factor out 3 = 3(x2 -(1/3)x + 4/3) add and subtract (1/6)2 = 3[x2 -(1/3)x + (1/6)2 - 1/36 + 4/3] simplify = 3[(x - 1/6)2 + 47/36] write 47/36 = - (-47/36) = - (√-1√47/6)2 = - (i√47/6)2 = 3[(x - 1/6)2 - (i√47/6)2] write the difference of the squares = 3[(x - 1/6) - (i√47/6)][(x - 1/6) + (i√47/6)] = 3[(x - (1 + i√47)/6)][(x - (1 - i√47)/6]. (MORE)